2003
DOI: 10.1084/jem.20030026
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Interleukin (IL)-12 p35 and p40 Gene Expression and Interferon (IFN)-γ–primed IL-12 Production by IFN Regulatory Factor 1

Abstract: Interleukin (IL)-12 is a heterodimeric cytokine consisting of the p40 and p35 chains encoded on separate chromosomes. Coordinated expression of the two constituent genes is crucial for appropriate immune responses in timing, location, and magnitude. Interferon (IFN)-γ priming of IL-12 production by macrophages represents an important physiological process in vivo for escalated cellular response to microbial infections. We provide evidence that IFN regulatory factor (IRF)-1–deficient macrophages have a selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
179
1
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(204 citation statements)
references
References 36 publications
19
179
1
5
Order By: Relevance
“…IL-12 is a proinflammatory cytokine, and the expression of its two subunits, p40 and p35, are known to be transcriptionally regulated by NF-κB and IRFs (Grumont et al, 2001;Liu et al, 2003;Maruyama et al, 2003;Masumi et al, 2002). Cameron et al found that the inhibition of LPS-induced IL-12 production in L. mexicana amastigote-infected MΦs was due to the degradation of IκB and NF-κB by amastigotes-derived cysteine peptidase B (Cameron et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…IL-12 is a proinflammatory cytokine, and the expression of its two subunits, p40 and p35, are known to be transcriptionally regulated by NF-κB and IRFs (Grumont et al, 2001;Liu et al, 2003;Maruyama et al, 2003;Masumi et al, 2002). Cameron et al found that the inhibition of LPS-induced IL-12 production in L. mexicana amastigote-infected MΦs was due to the degradation of IκB and NF-κB by amastigotes-derived cysteine peptidase B (Cameron et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…1 These chains are encoded by genes on different chromosomes and their production can be regulated independently. 2,3 IL-12 is produced by a number of cell types, including macrophages, neutrophilic granulocytes and dendritic cells (DCs). DCs may be the most important source of IL-12.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we sought to elucidate how ICSBP regulates IL-12 p35 gene transcription by first examining the response of the human IL-12 p35 promoter to the effects of ICSBP in a well established transient transfection system in RAW cells (12). Fig.…”
Section: Il-12 P40 and P70 Production Is Defective In Icsbp ϫ/ϫmentioning
confidence: 99%
“…Previous studies by us and others have revealed an intimate relationship between IRF-1, ICSBP, and IL-12 in that IRF-1 acts as a critical component of IFN-␥ signaling in the selective activation of the IL-12 p35 transcription (12) in synergy with LPS-mediated events (13,14) and that IRF-1 and ICSBP cooperatively regulate the transcription of IL-12 p40 gene in IFN-␥-amplified IL-12 production (15,16). In this work, we show that ICSBP and IRF-1, activated primarily by IFN-␥, also cooperate in their transcriptional activation of the IL-12 p35 gene by directly binding to a specific site in the human IL-12 p35 promoter.…”
mentioning
confidence: 99%